Integrated Clinical Practice: Evaluating the Collective Impact of Multidepartment Healthcare Collaboration on Patient Outcomes and Quality of Care—A Systematic Review (The Review of Diabetic Studies, 2025)
Integrated clinical practice has become a cornerstone in modern healthcare systems seeking to enhance patient outcomes, reduce fragmentation, and strengthen the continuity of care. This systematic review evaluates the collective impact of multidepartmental collaboration—encompassing nursing, laboratory medicine, pharmacy, radiology, emergency services, medical records, and allied health departments—on clinical performance, patient safety, and service efficiency. We systematically searched peer-reviewed literature published between 2016 and 2025 across PubMed, Scopus, Web of Science, and CINAHL. From an initial 3,212 records, 78 studies met the inclusion criteria. Findings demonstrate that integrated interdisciplinary workflows significantly improve diagnostic accuracy, reduce treatment delays, strengthen medication safety, enhance chronic disease management, and increase patient satisfaction. Collaborative models such as multidisciplinary team (MDT) meetings, integrated care pathways, electronic health information exchange, and interdepartmental handover systems were strongly associated with improved outcomes. However, challenges include communication gaps, role ambiguity, inconsistent protocols, and limited digital interoperability. This review concludes that integrated clinical practice is essential to achieving high-quality, patient-centered healthcare. It recommends strengthening digital integration, interprofessional training, and shared governance models to maximize collaborative effectiveness.